Revisiting the Portfolio Diversification Impact of Farmland - Lavelle, Brian A.; Yamamoto, Katherine (Journal of Accounting and Finance, 2024)
We examine the impact of farmland within a mixed asset portfolio consisting of U.S. stocks, bonds, Treasury Bills, real estate, and gold to determine farmland’s diversification benefits. Farmland returns are proxied via a U.S. Farmland Real Estate Investment Trust (F-REIT). Using both constrained and unconstrained asset allocation assumptions, we employ Markowitz Portfolio Optimization resulting in various asset allocation outcomes. We find farmland to be a suboptimal choice within a well-diversified portfolio despite possessing a low correlation with the other assets. By revisiting the portfolio impact of farmland, our results update findings in the literature which have been mixed and inactive in recent years. Additionally, our findings have meaningful implications for the average investor who is considering allocating investment into farmland.